2022
DOI: 10.1111/all.15485
|View full text |Cite
|
Sign up to set email alerts
|

Validated allergen exposure chamber is plausible tool for the assessment of house dust mite‐triggered allergic rhinitis

Abstract: Background: Allergen exposure chamber (AEC) is a clinical facility that allows exposure to allergenic airborne particles in controlled environment. Although AECs offer stable levels of airborne allergens, the validation of symptoms and other endpoints induced by allergen challenge is key for their recommendation as a plausible tool for the assessment of patients, especially in clinical research. This study aimed to demonstrate the reproducibility of defined clinical endpoints after AEC house dust mite (HDM) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Hossenbaccus et al [3] tested two different allergen concentrations and observed a mean peak TNSS of 5.74 at a modest concentration and 8.17 at a high concentration. Similarly, Zemelka-Wiacek et al [4] documented mean peak TNSS values >6 at higher allergen concentrations and 4–6 at the lowest tested concentration. Khayath et al [9] who also used a spray drying technique with allergen extract and normal saline, reported a positive dose-response relationship: mean TNSS >6 was found in 58% of participants at 15 ng/m 3 , in 63% at 25 ng/m 3 , and in 75% at 46 ng/m 3 Der p1 concentration.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Hossenbaccus et al [3] tested two different allergen concentrations and observed a mean peak TNSS of 5.74 at a modest concentration and 8.17 at a high concentration. Similarly, Zemelka-Wiacek et al [4] documented mean peak TNSS values >6 at higher allergen concentrations and 4–6 at the lowest tested concentration. Khayath et al [9] who also used a spray drying technique with allergen extract and normal saline, reported a positive dose-response relationship: mean TNSS >6 was found in 58% of participants at 15 ng/m 3 , in 63% at 25 ng/m 3 , and in 75% at 46 ng/m 3 Der p1 concentration.…”
Section: Discussionmentioning
confidence: 81%
“…Allergen material and particle size distributions differ, e.g., the Vienna Challenge Chamber (Austria) reported use of large particles >25 μm from dried raw material [2]. Kingston Environmental Exposure Unit (Canada), GA 2-LEN chamber (Germany), Biogenics Research Chamber (USA), and ALL-MED Allergen Exposure Chamber (Poland) also used dried raw material, though not selected by particle size [3][4][5][6]. In contrast, AARHUS (Denmark) exposure chamber described to have collected dust from office buildings or homes that was subsequently homogenized, with particle sizes <5 μm, dominating during exposure [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, an EAACI task force comprising worldwide clinicians, AEC providers and delegates from regulatory authorities has provided overviews of the similarities and differences of current AEC facilities with the aim of further harmonization 129 . An important step in this direction has been the compilation of technical validation data reported by international AEC providers, opening the path for the next step of AEC development, the clinical validation, for example, through a hybrid approach 130,131 …”
Section: Methods In Ait Development Programs: Current Standards and F...mentioning
confidence: 99%
“…129 An important step in this direction has been the compilation of technical validation data reported by international AEC providers, opening the path for the next step of AEC development, the clinical validation, for example, through a hybrid approach. 130,131…”
Section: Me Thods In Ait De Velopment Prog R Ams: Current S Tandards ...mentioning
confidence: 99%
“…The allergen exposure chamber is particularly useful for assessing the responses of patients to airborne allergens. By controlling the concentration of allergen released, symptomatic changes of patients across different allergen concentrations may be assessed [ 123 ]. However, the most widely used method is skin prick testing (SPT).…”
Section: In Vivo Biomarkersmentioning
confidence: 99%